Prognosis of resected intraductal papillary mucinous neoplasm of the pancreas: using revised 2017 international consensus guidelines - Min, Ji Hye; Kim, Young Kon; Kim, Honsoul; Cha, Dong lk; Ahn, Soohyun (Abdominal Radiology, 2020)
Purpose: Although there has been considerable effort to define pre-operative features to predict the malignant potential of intraductal papillary mucinous neoplasms (IPMNs), the prognostic value of pre-operative clinical and MRI features has not been assessed. The aim of this study was to determine pre-operative clinical and MRI features that are predictive of disease-specific death or recurrence in patients undergoing pancreatic resection for IPMNs. Methods: We performed a retrospective analysis of 167 patients (mean age, 65 years; 114 men and 53 women) who underwent pre-operative MRI and surgical resection of IPMN of pancreas between 2009 and 2019. We evaluated disease-specific survival (DSS) and recurrence-free survival (RFS). Prognostic factor analysis was performed using clinical and MRI features according to the 2017 international consensus guidelines. Results: Of 167 patients, 86 (51.5%) had benign IPMNs and 81 (48.5%) had malignant IPMNs (48 [28.7%] invasive carcinoma and 33 [19.8%] high grade). On multivariable analysis, mural nodule size (hazard ratio [HR], 1.11; 95% confidence interval [CI], 1.04–1.18 and HR 1.07; 95% CI 1.03–1.12) and obstructive jaundice (HR 5.01; 95% CI 1.44–17.46 and HR 5.60; 95% CI 2.42–12.99) were the significant variables that were associated with DSS and RFS. The presence of lymphadenopathy (HR 50.7; 95% CI 4.0–643.0; P = 0.002) was the significant factor for DSS. IPMNs with mural nodule showed a significantly lower 5-year DSS (83.7% vs. 100%, P value < 0.01) and RFS (73.1% vs. 95.0%, P value < 0.01) compared with IPMNs with no mural nodule. Conclusions: Mural nodule size on MRI and obstructive jaundice were prognostic markers in the pre-operative evaluation of patients with IPMN of pancreas.
Keywords: Aged; Carcinoma, Pancreatic Ductal; Female; Humans; Male; Neoplasm Recurrence, Local; Pancreas; Pancreatic Neoplasms; Prognosis; Retrospective Studies; Guideline; Magnetic resonance imaging; Pancreatic intraductal neoplasms; Prognosis